Nanomaterials-Based Electrochemical Immunosensors for Proteins - RUSLING, JAMES F. (2012)
For this special issue on 90 years of polarography, the following personal account describes how my early research in electrochemistry and polarography in the laboratory of Prof. Petr Zuman led to a major research effort in the determination of proteins for cancer detection and monitoring. It reviews the very recent history of nanoparticle labels and multiplexed detection in protein immunosensors. It then describes our journey of discovery that has led to ultrasensitive protein immunosensors achieved by combining nanostructured electrodes with particles labeled with up to ½ million enzymes that can detect down to as little as 1 fg mL(−1) protein in diluted serum. Our most mature multiple protein detection system is a microfluidic device with eight sensors coated with 5-nm gold nanoparticles that uses off-line protein detection with heavily labeled magnetic particles. This approach has led to reliable sub pg mL(−1) detection limits for multiple proteins, provides excellent correlation with referee ELISA methods, and is currently being used for validation of panels of biomarkers for oral and prostate cancer. The article ends with a section on future perspectives.